Speaking Ill of the Dead. - Sawyer, Susan (Speaking Ill of the Dead: Jerks in Histo., 2016)
Each volume in this series features fifteen to twenty short biographies of notorious bad guys, perpetrators of mischief, visionary if misunderstood thinkers, and other colorful antiheroes from the history of a given city, state, or region of the U.S. The villainous, the misguided, and the misunderstood all get their due in these entertaining yet informing books.